Accessible science - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The two leading magazines Nature and Science have opened a website on scientific news related to development issues. It has regional options, book reviews, job opportunities and a very handy How do I? section with practical tips for writing a...